Convertible bonds as backdoor equity financing - Stein, Jeremy C. (Journal of Financial Economics, 1992)
This paper argues that corporations may use convertible bonds as an indirect way to get equity into their capital structures when adverse-selection problems make a conventional stock issue unattractive. Unlike other theories of convertible bond issuance, the model here highlights: 1) the importance of call provisions on convertibles and 2) the significance of costs of financial distress to the information content of a convertible issue.